Principles of planning of the program providing of operational control of the aircrafts flights, using the flight information - Манежик, О. І.; Остапенко, О. С.; Манежик, I. O.; Радченко, В. А. (Problems of Informatization and Control, 2007)
The article includes the researches on main principles of planning of the program providing of operational control of the aircrafts flights owing to the data of onboard parametrical registers